2020
DOI: 10.21512/humaniora.v11i3.6682
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impacts of Internet Pornography Addiction on Adolescents

Abstract: The research aimed to reveal the impacts by adolescents who experienced internet addiction with pornographic content. It applied a qualitative approach, namely an instrumental case study. Participants were 18-25 years old, there were six adolescents who were obtained based on the initial screening, namely self-reporting through a pornography internet addiction questionnaire. The data were collected by in-depth interviews, observation, and documentation. Thematic analysis with NVivo 12 data management was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
2
14
0
4
Order By: Relevance
“…times, so too the effect on cognition is shown from their obsessivecompulsive thinking about sexual content. They always have a desire to see the photo or video repeatedly, which causes them to experience sleep disturbances due to visualizing the scene of sexual intercourse (Setyawati & Suryanto, 2020). Overall, the results of the study indicate that there is no benefit from pornography to adolescents, hence there is a significant relationship between exposure to pornographic material and risky sexual behavior (Awaluddin et al, 2015;Shallo & Mengesha, 2019;Grubbs et al, 2022), which not only does it affect physical or behavioral conditions, but the greatest implications of pornography can be seen on adolescent personality development, especially adolescent spiritual development (Kohut & Stulhofer, 2018).…”
Section: The Effects Of Pornography On Adolescent Sexual Behaviormentioning
confidence: 87%
See 1 more Smart Citation
“…times, so too the effect on cognition is shown from their obsessivecompulsive thinking about sexual content. They always have a desire to see the photo or video repeatedly, which causes them to experience sleep disturbances due to visualizing the scene of sexual intercourse (Setyawati & Suryanto, 2020). Overall, the results of the study indicate that there is no benefit from pornography to adolescents, hence there is a significant relationship between exposure to pornographic material and risky sexual behavior (Awaluddin et al, 2015;Shallo & Mengesha, 2019;Grubbs et al, 2022), which not only does it affect physical or behavioral conditions, but the greatest implications of pornography can be seen on adolescent personality development, especially adolescent spiritual development (Kohut & Stulhofer, 2018).…”
Section: The Effects Of Pornography On Adolescent Sexual Behaviormentioning
confidence: 87%
“…There is a significant association between exposure to SE electronic materials and risky sexual behaviors. (Setyawati et al, 2020) The impact of cognition is shown from their obsessivecompulsive thoughts on sexual content. They always have the desire to see those photos or video over again, which lead them to sleep disorders due to visualizing scenes of sexual intercourse.…”
Section: (Shallo and Mengesha 2019)mentioning
confidence: 99%
“…The beautiful women and good‐looking men on pornographic sites make these sites attractive to adolescents (Peter & Valkenburg, 2009). In a qualitative study conducted by Setyawati et al (2020), adolescents with internet addiction with pornographic content stated that they felt like something was missing when they could not watch porn, they could not sleep due to thinking over and over again, and they used the internet as a tool to satisfy their sexual needs. Also, problems such as isolation, loneliness, not wanting to do anything, and conflict with family and friends may be experienced in the adolescent period.…”
Section: Discussionmentioning
confidence: 99%
“…A body of research has shown that these phenomena are increasing among younger generation including students with hearing impairment (Häggstrӧm-Nordin et al, 2006;Wolak et al, 2007). Pornographic information through print content, television programmes, and other digital media has been reported to have the capability of increasing some socially unacceptable behaviours linked to adjustment problems such as sexual experimentation, unprotected sexual engagement, rape, withdrawal, unrealistic attitudes towards sex, sleep disorder among others (Setyawati et al, 2020;Siyoto et al, 2018;Tsitsika et al, 2009).…”
Section: Introductionmentioning
confidence: 99%